O ACORDO DE NÃO PERSECUÇÃO CIVIL NA LEI Nº 14.230, DE 2021 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The article analyzes the discipline of the civil non-prosecution agreement in article 17-B of Law No. 8.429, 1992, included by Law No. 14.230, of October 25, 2021. The instrument inaugurates the transition phase from litigation to consensus in the law for the defense of administrative probity, an unavailable and unassailable right until then. The expected results, the requirements for the execution of the agreement, the circumstances limiting the negotiation, the calculation of the amount of the damage caused to the public treasury, among other procedural aspects, with emphasis on the remedial character of the corruption of the integrity program. The proper use of Multiport Justice will be essential for the realization of the fundamental right to a republic of integrity, to encourage peaceful and alternative solutions to conflicts, and to achieve the Sustainable Development Goal No. 16, Peace, Justice and Effective Institutions, of the 2030 Agenda.